A global review of the Virgianidae (Ashgillian-Llandovery, Brachiopoda, Pentameroidea) - Jia-Yu, R (戎嘉余); Boucot, AJ (PALEONTOLOGICAL SOC INC, 1998)
A review of the Late Ordovician, chiefly mid-Ashgillian, to Early Silurian, Llandovenian, pentameroidean brachiopods, the Virgianidae, permits them to be assigned to three subfamilies (Virgianinae [10 genera assigned], Mariannaellinae [5 genera assigned], Pleurodiinae [2 genera assigned]). Diagnoses are presented for each subfamily, with comments on diagnostic characters for each genus and species. All the genera occur in what are interpreted to have been relatively low latitude, warm water environments in Arctic North America, northern Europe, northern Asia, central Asia and South China; the presence of Australian Ordovician virgianids is uncertain at this time. The mid-Ashgillian pentameroid adaptive radiation was followed by latest Ordovician mass extinction, subsequently surviving recovery and radiation in the middle-late Llandovery. Silurian radiations convergently mimicked the Ordovician event in many respects.